A solar cell array structure and its application in solar airship
By designing a combined structure of the capsule material layer, phase change temperature regulation layer and heat insulation layer in a solar airship, the problem of overheating of the airship caused by solar cell array is solved, and effective thermal management and improvement of airship stability is achieved.
Patent Information
- Application Number
- CN202211105799.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-09-09
AI Technical Summary
In the prior art, the thermal management of solar cell arrays in airships is immature, resulting in overheating of the airship's capsule material and may lead to blasting accidents.
A solar cell array structure is designed, including a capsule material layer, a phase change temperature regulation layer A, a heat insulation layer, a phase change temperature regulation layer B and a flexible solar cell array. The phase change temperature regulation layer absorbs and releases heat through the phase change bonding material to regulate the internal temperature of the airship.
Without adding an adhesive layer, this structure realizes a close connection between the solar cell array and the capsule material, effectively absorbs heat generated by the battery array, reduces changes in the temperature inside the airship, and improves the stability and safety of the airship.
Smart Images

Figure CN115663051B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of airship bladder materials, and in particular relates to a solar cell array structure and an application in a solar airship. Background Art
[0002] Stratospheric airships are widely used in military and social service fields such as earth observation, communication and navigation, missile early warning, and cargo transportation.
[0003] Solar cells are used as energy sources for high-altitude navigation in the stratosphere. Due to their low light-to-electricity conversion efficiency, most of the light energy is still converted into heat energy. This heat directly acts on the airship capsule, causing the temperature of the gas inside the capsule to rise and the volume to increase, resulting in changes in the buoyancy and center of mass of the airship. In severe cases, the capsule may explode, leading to accidents. Therefore, thermal management of solar cell arrays is crucial.
[0004] Normally, a layer of foam is introduced between the solar cell array and the bladder material to provide a certain degree of thermal insulation. Song Linlin et al. proposed a new lightweight thermal insulation solar cell module structure in the "Research on Thermal Insulation Technology of Lightweight Solar Cell Modules for Stratospheric Airships", including a PI layer / carbon fiber / epoxy resin / PMI foam under the solar cell. This structure can achieve a thermal insulation effect of not less than 30°C on a lightweight structure. However, in actual application, the solar airship equipped with thermal insulation foam still overheated at the solar cell array, causing the hull to rupture and disintegrate in the air.
[0005] At present, the heat treatment technology for solar cell arrays in airships is not mature. Only the edges of the solar cell arrays are fixed, and there is no connection with the insulation foam in the middle. This causes the air temperature between the foam and the solar array to rise seriously, and the foam insulation effect is not ideal. At the same time, due to the unreliable connection, it is easy to break when subjected to uneven external forces. Summary of the invention
[0006] The present invention provides a solar cell array structure and its application in a solar airship. The solar cell array structure of the present invention achieves a close connection between layers without adding an additional adhesive layer, and provides a temperature regulating effect, thereby effectively absorbing the heat generated when the solar cell array is working.
[0007] The present invention provides a solar cell array structure, comprising a capsule material layer, a phase change temperature adjustment layer A, a heat insulation layer, a phase change temperature adjustment layer B and a flexible solar cell array, which are in contact with each other in sequence;
[0008] The phase change temperature adjustment layer A and the phase change temperature adjustment layer B are always in a solid state during the phase change process and play an interlayer bonding role. The phase change temperature adjustment layer A and the phase change temperature adjustment layer B include a phase change bonding material;
[0009] The phase change adhesive material comprises a polymer matrix and a phase change functional segment chemically bonded to the polymer matrix; wherein the mass fraction of the phase change functional segment is 50-90wt%.
[0010] The polymer matrix includes one or more of low-density polyethylene, ethylene-vinyl acetate copolymer, polyacrylic acid compound and polyurethane; the phase change functional segment includes paraffin and / or polyethylene glycol.
[0011] Preferably, the thickness of the phase change temperature adjustment layer A is 0.1-1.0 mm; the thickness of the phase change temperature adjustment layer B is 0.1-1.0 mm.
[0012] Preferably, the melting point of the phase change adhesive material is 30-60°C.
[0013] Preferably, the enthalpy value of the phase change adhesive material is 60-200 J / g.
[0014] Preferably, the capsule layer has a thickness of 100 to 300 μm.
[0015] Preferably, the thermal insulation layer is aerogel felt and / or foam.
[0016] Preferably, the thermal insulation layer is one or more of a silica aerogel thermal insulation layer, a cellulose aerogel thermal insulation layer, a polyurethane foam thermal insulation layer, a polystyrene foam thermal insulation layer and a polyimide foam thermal insulation layer.
[0017] Preferably, the thickness of the heat insulation layer is 0.1 to 2 cm.
[0018] The present invention provides application of the solar cell array structure as described above in a solar airship.
[0019] The present invention provides a solar cell array structure, comprising a capsule material layer, a phase change temperature regulating layer A, a heat insulation layer, a phase change temperature regulating layer B and a flexible solar cell array in contact with each other in sequence; the phase change temperature regulating layer A and the phase change temperature regulating layer B are always in a solid state during the phase change process and play an interlayer bonding role, and the phase change temperature regulating layer A and the phase change temperature regulating layer B include a phase change bonding material; the phase change bonding material includes a polymer matrix and a phase change functional segment chemically bonded to the polymer matrix; the polymer matrix includes one or more of low-density polyethylene, ethylene-vinyl acetate copolymer, polyacrylic acid compound and polyurethane; the phase change functional segment includes paraffin and / or polyethylene glycol. In the present invention, the phase change layer is a flexible matrix, which can not only serve as an adhesive layer to improve the bonding strength between the layers, but also absorb part of the heat generated by the solar cell back panel. At the same time, when solar energy cannot work at night, the stored heat can be released, effectively delaying the rate and amplitude of change of the gas temperature inside the airship; the heat insulation layer can block the remaining part of the heat, so it can effectively reduce the influence of the heat generated by the solar cell on the temperature and air pressure inside the airship, and improve the stability of the airship. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0021] Figure 1 is a schematic structural diagram of a solar cell array of the present invention,
[0022] Figure 1 In the figure, 1 is a solar cell array; 2 is a phase change temperature regulating layer B; 3 is a heat insulation layer; 4 is a phase change temperature regulating layer A; 5 is a capsule material layer;
[0023] Figure 2 This is a diagram of a thermal control effect test device for a multi-layer structure for a solar airship in an embodiment of the present invention, wherein the multi-layer structure for a solar airship is placed in thermal insulation foam, and temperature measuring points are set at three points a, b, and c; wherein a is behind the solar cell array backplane; b is in front of the capsule material layer; and c is behind the capsule material layer. DETAILED DESCRIPTION
[0024] The present invention provides a solar cell array structure, comprising a capsule material layer, a phase change temperature adjustment layer A, a heat insulation layer, a phase change temperature adjustment layer B and a flexible solar cell array, which are in contact with each other in sequence;
[0025] The phase change temperature adjustment layer A and the phase change temperature adjustment layer B are always in a solid state during the phase change process and play an interlayer bonding role. The phase change temperature adjustment layer A and the phase change temperature adjustment layer B include a phase change bonding material;
[0026] The phase change adhesive material comprises a polymer matrix and a phase change functional segment chemically bonded to the polymer matrix;
[0027] The polymer matrix includes one or more of low-density polyethylene, ethylene-vinyl acetate copolymer, polyacrylic acid compound and polyurethane; the phase change functional segment includes paraffin and / or polyethylene glycol.
[0028] The solar cell array in the present invention has a simple structure. Without introducing an adhesive layer, it can achieve a close connection between the solar cell array, the insulation foam and the bladder material, while effectively improving the stability of the temperature and air pressure of the gas inside the airship, reducing the influence of the solar cell array on the temperature inside the airship, and improving the safety and stability of the airship.
[0029] In the present invention, the capsule material layer is a common capsule material layer in the art, including a weather-resistant layer / barrier layer / load-bearing layer / heat-sealing layer or a barrier layer / load-bearing layer / heat-sealing layer. The material of each layer can be a capsule material layer commonly used in the art, and the present invention will not repeat them here. The thickness of the capsule layer is preferably 100 to 300 μm, more preferably 150 to 250 μm.
[0030] In the present invention, the phase-change temperature-adjusting layer A includes a phase-change adhesive material, and the phase-change adhesive material includes a polymer matrix and a phase-change functional segment chemically bonded to the polymer matrix; the polymer matrix is preferably one or more of low-density polyethylene (LDPE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA) and polyurethane (PU); the phase-change functional segment is preferably paraffin and / or polyethylene glycol. In the present invention, the proportion of the phase-change functional segment in the phase-change adhesive material is preferably 50-90wt%, more preferably 60-80wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, preferably a range value with any of the above values as the upper or lower limit.
[0031] The melting point of the phase change adhesive material is preferably 30-60°C, more preferably 40-50°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, preferably a range value with the above any numerical value as the upper or lower limit; the enthalpy value of the phase change adhesive material is preferably 60-200 J / g, more preferably 100-150 J / g, such as 60 J / g, 70 J / g, 80 J / g, 90 J / g, 100 J / g, 110 J / g, 120 J / g, 130 J / g, 140 J / g, 150 J / g, 160 J / g, 170 J / g, 180 J / g, 190 J / g, 200 J / g, preferably a range value with the above any numerical value as the upper or lower limit.
[0032] The preparation method of the phase change adhesive material is a conventional grafting method or a block method. It mainly includes the following steps:
[0033] (1) Modify the polymer matrix so that it has reactive side groups or end groups.
[0034] (2) Paraffin wax or modified paraffin wax or polyethylene glycol is reacted with the side group or end group of the polymer matrix to obtain a comb-shaped or block phase change adhesive material.
[0035] In the present invention, the thickness of the phase change temperature adjustment layer A is preferably 0.1-1.0 mm, more preferably 0.3-0.8 mm, such as 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, preferably a range value with any of the above values as the upper or lower limit.
[0036] In the present invention, the thermal insulation layer is preferably a porous material, such as aerogel felt and / or foam material, more preferably one or more of a silica aerogel insulation layer, a cellulose aerogel insulation layer, a polyurethane foam insulation layer, a polystyrene foam insulation layer and a polyimide foam insulation layer; the thickness of the thermal insulation layer is preferably 0.1-2 cm, more preferably 0.5-1.5 cm, such as 0.1 cm, 0.2 cm, 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, 0.9 cm, 1.0 cm, 1.1 cm, 1.2 cm, 1.3 cm, 1.4 cm, 1.5 cm, 1.6 cm, 1.7 cm, 1.8 cm, 1.9 cm, 2.0 cm, preferably a range value with any of the above values as the upper or lower limit.
[0037] In the present invention, the phase change temperature regulating layer B preferably includes a phase change adhesive material, and the phase change adhesive material includes a polymer matrix and a phase change functional segment chemically bonded to the polymer matrix; the polymer matrix is preferably one or more of low-density polyethylene (LDPE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA) and polyurethane (PU); the phase change functional segment is preferably paraffin and / or polyethylene glycol.
[0038] The melting point of the phase change adhesive material is preferably 30-60°C, more preferably 40-50°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, preferably a range value with the above any numerical value as the upper or lower limit; the enthalpy value of the phase change adhesive material is preferably 60-200 J / g, more preferably 100-150 J / g, such as 60 J / g, 70 J / g, 80 J / g, 90 J / g, 100 J / g, 110 J / g, 120 J / g, 130 J / g, 140 J / g, 150 J / g, 160 J / g, 170 J / g, 180 J / g, 190 J / g, 200 J / g, preferably a range value with the above any numerical value as the upper or lower limit.
[0039] In the present invention, the specific components of the phase change temperature adjustment layer B and the phase change temperature adjustment layer A may be the same or different.
[0040] During the entire phase transition process, the phase change thermostatic layers A and B are always in a solid state, and there will be no leakage or flow of the melt; at the same time, within a certain temperature range, the molecular chain of the phase change material layer moves and can act as an adhesive layer, improving the bonding between the solar cell array, the thermal insulation foam and the capsule material, and ensuring the structural stability. The phase change thermostatic layers A and B used in conjunction with the thermal insulation foam can absorb and release part of the heat of the solar cells during operation, delaying the impact of the solar cells on the gas inside the airship, and improving the stability of the airship.
[0041] In the present invention, the thickness of the phase change temperature adjustment layer B is preferably 0.1-1.0 mm, more preferably 0.3-0.8 mm, such as 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, preferably a range value with any of the above values as the upper or lower limit.
[0042] In the present invention, the solar cell array is a solar cell array commonly used in the art, and the present invention will not be described in detail herein.
[0043] The present invention also provides an application of the solar cell array structure described above in a solar airship. The solar cell array structure in the present invention is used in the battery array portion of the solar airship.
[0044] In order to further illustrate the present invention, a solar cell array structure provided by the present invention and its application in a solar airship are described in detail below in conjunction with embodiments, but this should not be construed as limiting the protection scope of the present invention.
[0045] Example 1
[0046] The solar cell array structure in this embodiment is as follows Figure 1 As shown, the phase change material layer I is EVA with a melting temperature of ~30°C, an enthalpy value of 60J / g, and a thickness of 1mm, wherein the phase change functional segment is a carboxylate of paraffin, accounting for 50wt%; the thermal insulation layer is a silica aerogel felt with a thickness of 0.1cm; the capsule materials are weather-resistant layer / barrier layer / adhesive layer / load-bearing layer / heat-sealing layer from the outside to the inside.
[0047] The preparation method of the phase change material layer I is as follows:
[0048] a. Weigh 20g EVA and dissolve it in 100ml dichloromethane, add 1.5g N-hydroxysuccinimide (NHS) and 3.0g N,N'-dicyclohexylcarbodiimide (DCC), and react at 0-30℃ for 3-6h. Use deionized water for dialysis and dry to obtain the intermediate product.
[0049] b. Dissolve the above product in tetrahydrofuran, add 26 g of polyoxyethylene monomethyl ether or fatty alkyl acid and 1.5 g of 4-dimethylaminopyridine (DMAP), and react at 40-70°C for 140-200 h.
[0050] c. Then, the product was filtered, the filtrate was taken and centrifuged, the supernatant was retained, and then poured into chloroform to precipitate the product, which was washed with ethyl acetate and then dried for molding.
[0051] At the same time, three structures including solar cell array / bladder material layer, solar cell array / phase change material layer / bladder material layer and solar cell array / thermal insulation foam / adhesive layer / bladder material layer were used as control 1, control 2 and control 3.
[0052] To evaluate the thermal control effect of the structure, the multilayer structure was placed in thermal insulation foam and outdoor tests were carried out on a sunny summer day. Figure 2 The light intensity was measured by a solar power meter, and the average irradiance was ~1100W / m 2 Among them, the temperature test point a of the control sample 1 is after the solar cell array, and b is after the capsule material; the temperature test point a of the control sample 2 and the embodiment is after the solar cell array, b is before the capsule material, and c is after the capsule material.
[0053] Embodiments 2 to 4
[0054] Different from Example 1, in Examples 2-5, a multilayer structure for a solar airship is provided, and the enthalpy values of the phase change material layer are 100 J / g, 150 J / g and 200 J / g respectively.
[0055] Embodiments 5 to 7
[0056] Different from Example 2, in Examples 5-7, a multilayer structure for a solar airship is provided, and the thickness of the phase change material layer is 0.7 mm, 0.5 mm and 0.1 mm respectively.
[0057] Embodiments 8 to 10
[0058] Different from Example 2, Examples 8-10 provide a multilayer structure for a solar airship, and the phase change melting points of the phase change layers thereof are ∼40°C, ∼50°C and ∼60°C.
[0059] Table 1 shows the average irradiation intensity of each part of the multilayer structure in Examples 1 to 10 at 1100 W / m 2 The temperature after being exposed to sunlight for 1 hour.
[0060] Table 1
[0061]
[0062] It can be seen from Table 1 that as the enthalpy value of the phase change material layer increases, the temperature before and after the capsule material layer decreases; when the enthalpy value is the same, the temperature before and after the capsule material layer decreases as the thickness of the phase change material layer increases; when the enthalpy value and thickness are similar, when the phase change melting point is less than 60°C, the temperature before and after the capsule material layer is not greatly correlated with the phase change melting point.
[0063] Examples 11 to 13
[0064] Different from Example 2, in the multilayer structure for solar airship provided in Examples 11-13, the matrix of the phase change temperature regulating layer is PU, LLDPE and PAA respectively, and the phase change functional segments are all polyethylene glycol, accounting for 90wt%.
[0065] The preparation steps of PU are as follows:
[0066] a. Weigh 10g of polyethylene glycol and dissolve it in 10ml of anhydrous DMF. Add 10ml of DMF solution containing 2.5g of diisocyanate dropwise and react at 60℃ for 2h to obtain a prepolymer.
[0067] b. Add 5 ml of DMF solution containing 0.9 g of chain extender and continue to react at 80°C for 2 h. Then pour the solution directly into the mold and dry it at 100°C to form a film.
[0068] Embodiments 14 to 16
[0069] Different from Example 2, the multi-layer structure for a solar airship provided in Examples 14-16 is a solar cell array / phase change temperature control layer I / thermal insulation foam layer / phase change temperature control layer II / bladder material layer, wherein the phase change temperature control layer I is the same as Example 2; the phase change temperature control layer II is the same as Examples 11-13 respectively.
[0070] Embodiments 17 to 19
[0071] Different from Example 14, the melting points of the phase change temperature adjustment layer II in Examples 17-19 are respectively ∼40°C, ∼50°C and 60°C.
[0072] Table 2 shows the average irradiation intensity of each part of the multilayer structure in Examples 11-19 at 1100 W / m 2 The temperature after being exposed to sunlight for 1 hour.
[0073] Table 2
[0074]
[0075] It can be seen from Table 2 that the polymer matrix of the phase change temperature regulating layer has no effect on the temperatures in the multilayer structure of the airship. When the phase change melting point is less than 60°C, the temperature before and after the capsule material layer has little correlation with the phase change melting point.
[0076] Embodiments 20 to 22
[0077] Different from Example 2, in the multi-layer structure for a solar airship provided in Examples 20-22, the thickness of the aerogel felt used in the heat insulation layer is 0.5 cm, 1.0 cm and 2.0 cm respectively.
[0078] Embodiments 23 to 26
[0079] Different from Example 2, Examples 23-26 provide a multilayer structure for a solar airship, wherein the heat insulation layer is cellulose aerogel, polystyrene foam, polyurethane foam and polyimide foam.
[0080] Table 3 shows the average irradiation intensity of each part of the multilayer structure in Examples 20-26 at 1100 W / m 2 The temperature after being exposed to sunlight for 1 hour.
[0081] Table 3
[0082]
[0083] It can be seen from Table 3 that as the thickness of the thermal insulation layer increases, the temperature before and after the bladder material decreases; the thermal insulation effects of different types of thermal insulation layers are not much different.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A solar cell array structure, comprising a capsule material layer, a phase change temperature adjustment layer A, a heat insulation layer, a phase change temperature adjustment layer B and a flexible solar cell array in contact with each other in sequence; The phase change temperature adjustment layer A and the phase change temperature adjustment layer B are always in a solid state during the phase change process and play an interlayer bonding role. The phase change temperature adjustment layer A and the phase change temperature adjustment layer B include a phase change bonding material; The phase change adhesive material comprises a polymer matrix and a phase change functional segment chemically bonded to the polymer matrix; wherein, The mass fraction of the phase change functional segment is 50 to 90 wt%; The polymer matrix includes one or more of low-density polyethylene, ethylene-vinyl acetate copolymer, polyacrylic acid compound and polyurethane; the phase change functional segment includes paraffin and / or polyethylene glycol; The polyurethane is prepared according to the following steps: 10 g of polyethylene glycol is weighed and dissolved in 10 ml of anhydrous DMF; 10 ml of a DMF solution containing 2.5 g of diisocyanate is added dropwise, and the mixture is reacted at 60° C. for 2 h to obtain a prepolymer; 5 ml of a DMF solution containing 0.9 g of a chain extender is added, the mixture is reacted at 80° C. for 2 h, and the solution is directly poured into a mold and dried at 100° C. to form a film; The heat insulation layer is one or more of a silicon dioxide aerogel heat insulation layer, a cellulose aerogel heat insulation layer, a polyurethane foam heat insulation layer, a polystyrene foam heat insulation layer and a polyimide foam heat insulation layer.
2. The solar cell array structure according to claim 1, characterized in that: The thickness of the phase change temperature adjustment layer A is 0.1-1.0 mm; the thickness of the phase change temperature adjustment layer B is 0.1-1.0 mm.
3. The solar cell array structure according to claim 1, characterized in that: The melting point of the phase change adhesive material is 30-60°C.
4. The solar cell array structure according to claim 1, characterized in that: The enthalpy value of the phase change adhesive material is 60-200 J / g.
5. The solar cell array structure according to claim 1, characterized in that: The thickness of the capsule material layer is 100-300 μm.
6. The solar cell array structure according to claim 1, characterized in that: The thickness of the heat insulation layer is 0.1-2 cm.
7. Application of the solar cell array structure as claimed in claim 1 in a solar airship.
Citation Information
Patent Citations
Flexible netlike solar battery array for stratospheric aerostat
CN103280472A
Composite phase change material and application thereof, and product
CN112625423A
Double -sided solar battery component
CN206076251U
Bag skin and aerostatics
CN207250536U